Breath-Hold Blood Oxygen Level–Dependent MRI: A Tool for the Assessment of Cerebrovascular Reserve in Children with Moyamoya Disease - Dlamini, N.; Shah-Basak, P.; Leung, J.; Kirkham, F.; Shroff, M.; Kassner, A.; Robertson, A.; Dirks, P.; Westmacott, R.; deVeber, G.; Logan, W. (American journal of neuroradiology : AJNR, 2018)
There is a critical need for a reliable and clinically feasible imaging technique that can enable prognostication and selection for revascularization surgery in children with Moyamoya disease. Blood oxygen level-dependent MR imaging assessment of cerebrovascular reactivity, using voluntary breath-hold hypercapnic challenge, is one such simple technique. However, its repeatability and reliability in children with Moyamoya disease are unknown. The current study sought to address this limitation. Children with Moyamoya disease underwent dual breath-hold hypercapnic challenge blood oxygen level-dependent MR imaging of cerebrovascular reactivity in the same MR imaging session. Within-day, within-subject repeatability of cerebrovascular reactivity estimates, derived from the blood oxygen level-dependent signal, was computed. Estimates were associated with demographics and intellectual function. Interrater reliability of a qualitative and clinically applicable scoring scheme was assessed. Twenty children (11 males; 12.1 ± 3.3 years) with 30 MR imaging sessions (60 MR imaging scans) were included. Repeatability was "good" on the basis of the intraclass correlation coefficient (0.70 ± 0.19). Agreement of qualitative scores was "substantial" (κ = 0.711), and intrarater reliability of scores was "almost perfect" (κ = 0.83 and 1). Younger participants exhibited lower repeatability ( = .027). Repeatability was not associated with cognitive function ( > .05). However, abnormal cerebrovascular reactivity was associated with slower processing speed ( = .015). Breath-hold hypercapnic challenge blood oxygen level-dependent MR imaging is a repeatable technique for the assessment of cerebrovascular reactivity in children with Moyamoya disease and is reliably interpretable for use in clinical practice. Standardization of such protocols will allow further research into its application for the assessment of ischemic risk in childhood cerebrovascular disease.